The Analysis Of 3 Phase 1 HP Induction Motor Efficiency In Under Voltage And Over Voltage Condition With PSIM Simulation - Sohih Ajie Prabowo; Wakhyu Dwiono; Arif Johar Taufiq (LEMBAGA PUBLIKASI ILMIAH DAN PENERBITAN, UNIVERSITAS MUHAMMADIYAH PURWOKERTO, 2019)
Three phase induction is the most common motor and is widely used in various industrial equipment because of all the advantages. To get the best performance, the quality of powersupply of induction motors needs to be maintained. One of the problems that arise in power quality is under voltage or over voltage. In this study the calculation and analysis of efficiency using the segregated loss method of 3 phase induction motors connected to stars and delta on the under voltage and over voltage conditions of the rating voltage, and at the rating voltage, the motor used is a 3 Phase 1 HP 4 pole induction motor with voltage rating of 380 volts. The method used is the segregated loss method, this method is a method to get the value of the efficiency of the induction motor by finding and separating the value of loss and loss, the method used refers to IEEE 112. Simulation using PSIM software as a hypothesis and comparison, variables taken are speed, current, inter-phase voltage and input power. Based on the results of calculations from all experiments show that the induction motor will produce better efficiency at loads approaching its capacity, and under voltage and over voltage conditions affect the efficiency value with a small difference in each change in voltage conditions. Efficiency values in all star motor voltage conditions range between 44% - 52% and in delta connection motor ranges between 39% - 42%. Simulations carried out using PSIM software produce higher efficiency than the test results with a range of values of 67% -78%, where the value is calculated from the simulation results and ignoring core losses.